Rede integrada de infraestrutura: Atores do Sistema Nacional de Viaç\~ao segundo a legislaç\~ao - Jean Marlo Pepino de Paula (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The purpose of this work is to identify the institutional network of the National Road System (SNV) to illustrate and discuss its complexity. A qualitative-quantitative analysis of legislation permitted to circumscribe objectives and limits and to identify key members and interactions. This showed that there is a limitation and mismatch of information that may hinder its understanding and compromise the synergy of a complex institutional network, allowing recent legal changes purged important players to the SNV interact in a macro context, for example. Furthermore, it was possible to identify the high involvement of actors that are not very evident in the processes of public policy making but important for the results in a macro context. In a timely manner, the work presents a map with the institutional network of the SNV, which contributes to a greater understanding of a broader and more complete scenario of the Brazilian transport system.
Keywords: H41; L78; O17; O18; 330; National Road System; system approach; infrastructure; transport